Benefits of ginger in the control of chemotherapy-induced nausea and vomiting - Borges, Dayane Oliveira [UNESP]; Batista da Silva Freitas, Karina Alexandra [UNESP]; Minicucci, Eliana Maria [UNESP]; Popim, Regina Celia [UNESP] (Assoc Brasileira Enfermagem, 2020)
Objectives: To identify and discuss scientific evidence of the effects of ginger use on the management of chemotherapy-induced nausea and vomiting. Methods: This is an integrative review performed by Ganong's reference. Results: We included 24 studies, highlighting three thematic categories, namely 1) antiemetic action of ginger - nausea (13 articles; of these, nine significant) and emesis (10 studies; of these, six significant); 2) action in the control of nausea (11 articles; of these, six significant) and vomiting (8 articles; of these, three significant) in the acute phase; 3) action in the control of nausea (6 articles; of these, three significant) and vomiting (6 articles; of these, three significant) in the delayed phase. There were divergences of the methods used. Final considerations: This complementary therapy has low cost and easy access, but no statistical confirmation of its effectiveness in the management of nausea and vomiting in cancer patients was found.
Keywords: Nausea; Vomiting; Chemotherapy; Ginger; Zingiber Officinale